It’s not black and white: Perspectives of Western Canadian beef farmers on dairy-beef production - Bianca Vandresen; Daniel M. Weary; Marina A. G. von Keyserlingk (PLoS ONE, 2025)
Non-replacement dairy calves (i.e., males and females not needed for milking herd replacement) can face multiple welfare challenges due to their low economic value in the dairy and beef industries. Incorporating beef genetics into dairy herd breeding programs has become common to produce beef-on-dairy crossbred calves that are better suited for beef production than pure dairy breed animals. This practice has the potential to increase revenue from non-replacement dairy calves for dairy farmers, but little is known about its impact on beef farmers. This study aimed to investigate the attitudes of Canadian beef producers toward dairy-beef production, with a focus on how beef-on-dairy breeding strategies by dairy may affect the beef industry. We conducted semi-structured interviews with 20 beef farmers in Western Canada, exploring their awareness, attitudes, and recommendations for the management of beef-on-dairy calves. Participants (11 male, 9 female) were recruited using snowball sampling and interviewed following a semi-structured interview guide. The audio-recorded interviews (averaging 44 ± 15 min in duration) were transcribed verbatim and analyzed using inductive thematic analysis, resulting in three main themes: 1) the dairy and beef relationship, 2) attitudes to beef-on-dairy animals, and 3) a shared future. In the first theme, participants discussed the relationship between the dairy and beef industries, highlighting differences in Canadian market structures (dairy as supply-managed vs. beef as an open market), farming practices (beef as more extensive vs. dairy as more intensive) and public perceptions of the two systems. In the second theme, participants showed mixed attitudes toward dairy-beef production and discussed their views about beef-on-dairy calves compared to purebred dairy calves, the management practices used to raise them, and the potential impacts of dairy-beef production on the beef industry. In the third theme, participants reflected on the future of dairy-beef production, discussing who should be involved in shaping the future of this practice. Participants showed mixed feelings towards the use of beef genetics in dairy herds, with some perceiving this as an opportunity for the beef industry to meet consumer demand and others expressing concern about the over-saturation of the beef market and possible threats to traditional ways of rearing beef. Our study enhances the understanding of the relationship between the dairy and beef industries in Western Canada and suggests the need for communication and collaboration among producers and others in the supply chain.